Zinc Supplementation Improves Nocturnal Asthma Symptoms - Iman Abdelaziz; Magd Ahmed Kotb; Noha Adel Yassin; Walaa Ahmed Rabie; Alsayed Fathy Alsayed; Dina Hossam Hamed (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Treatment of bronchial asthma aims to control the symptoms of bronchoconstriction and disease modification. Zinc influences bradykinin that promotes inflammation and promotes contraction of smooth muscle in the bronchus. Aim of the work: To test the effect of zinc supplementation on improvement of both clinical symptoms and lung functions in children with bronchial asthma. Methods: Asthma symptoms, severity and pulmonary function tests were performed to 50 children with bronchial asthma before and after zinc supplementation (1mg/kg/ day) as adjuvant therapy. Serum zinc levels were assessed at initial enrollment for all 50 children. Results: The studied cohort comprised 28 boys and 22 girls with age range of 6-13 years and mean age +/- SD of 8.88 +/- 2.24 years. Of them 48 %, 30 % and 22% were diagnosed: moderate persistent asthma, mild persistent and severe persistent asthma respectively. Initial serum zinc level was low in 34% of patients (mean 47.2 ±10.8 μg/dl) and 66% of patients had a normal initial serum zinc level (mean 100.6 ± 27.2 μg/dl). After 8 weeks of zinc supplementation there was a significant improvement in decreasing frequency of attacks (p=0.036), nocturnal symptoms (p˂ 0.001), clinical control of asthma symptoms (p˂ 0.001) and pulmonary functions showed significant improvement in forced expiratory volume in 1 second (FEV1) (p˂0.001) and forced vital capacity (FVC) (p=0.002) but there was no significant difference in the frequency of daytime symptoms (p˃0.05), limitation of activities (p˃0.05) or need for reliever medications (p˃0.05). Conclusion: Zinc is an effective adjuvant in controlling nocturnal symptoms and significantly improves pulmonary functions even if the initial serum zinc level was within the normal range.